Microwave Sensing of Sugar Solution Concentration Using a 2.4 GHz Microstrip Antenna - Andre, Hanalde; Nelson, Jimmy; Pratama, Rizki Wahyu; Zaky, Toha (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2026)
Microstrip antennas are widely used in sensing applications according to compact, low-cost, and easy to fabricate. This study presents the design and evaluation of a 2.4 GHz circular patch microstrip antenna integrated with a split-ring resonator (SRR) for sensing sugar-solution concentration through dielectric property induced perturbations. The antenna employs an inset feed configuration and is implemented on an FR4 substrate. The design and parametric analysis are carried out in simulation by placing sugar solutions with mole fractions from 0 to 0.04 in the sensing region. In result, we observe changes in resonant frequency, minimum return loss, and quality factor (Q). The simulations indicate monotonic trends with concentration, with the minimum return loss becoming less negative as concentration increases, accompanied by reductions in resonant frequency and Q. Experimental measurements of the fabricated prototype, however, show weaker and less consistent correlations across the same parameters, highlighting the sensitivity of the response to practical factors such as sample positioning, fabrication tolerances, and measurement repeatability